Collaboration Meeting with LKPP Corporation Sdn. Bhd. - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 18 June 2021 – There was a collaboration meeting held virtually between FK and LKPP Corporation Sdn. Bhd.